Does association of opioid use with pain and function differ by fibromyalgia or widespread pain status?. Issue 10 (October 2016) - Turner, Judith A.; Shortreed, Susan M.; Saunders, Kathleen W.; LeResche, Linda; Thielke, Stephen; Von Korff, Michael
Abstract : Abstract: Many consider chronic opioid therapy (COT) to be ineffective for fibromyalgia, but empirical evidence is limited. Among patients identified as initiating COT, we examined whether fibromyalgia was associated with different relationships of opioid use to pain and activity interference outcomes 12 months later. We obtained electronic data on diagnoses and opioid prescriptions. We obtained patient self-report data, including pain and activity interference measures, at baseline, 4 months, and 12 months. Among 1218 patients, 429 (35%) met our definition of fibromyalgia. Patients with and without fibromyalgia who had intermittent/lower-dose or regular/higher-dose opioid use at 12 months had similar 12-month pain intensity scores. However, among patients with minimal/no opioid use at 12 months, 12-month pain intensity was greater for those with fibromyalgia (adjusted mean = 5.15 [95% confidence interval, 4.80–5.51]; 0-10 scale) than for those without (4.44 [4.15–4.72]). Similar patterns were observed for 12-month activity interference. Among patients who discontinued opioids by 12 months, those with fibromyalgia were more likely to report bothersome side effects and less likely to report pain improvement as important reasons for discontinuation ( P < 0.05). In sum, at 12 months, among patients who had discontinued opioids or used them minimally, those with fibromyalgia had worse outcomes and were less likely to have discontinued because of pain improvement. Among patients continuing COT, pain and activity interference outcomes were worse than those of patients with minimal/no opioid use and did not differ for those with fibromyalgia vs those with diverse other chronic pain conditions. Abstract : Supplemental Digital Content is Available in the Text.Among patients who sustained long-term opioid use for chronic pain, pain and function outcomes did not differ for those with fibromyalgia.